Resiliensi Psikospiritual dalam Perspektif Kristen: Sebuah Analisis Teologis-Psikologis - Avlorina, Mey (Sekolah Tinggi Teologi Injili Indonesia Palu, 2025)
This article examines the concept of psychospiritual resilience from a Christian perspective using a theological-psychological analysis approach. In a world full of emotional stress and existential crises, resilience is seen not only as the ability to mentally survive but also as an active faith response to suffering. This research uses a qualitative descriptive approach with a literature review to examine the interaction between Christian doctrine, spiritual experience, and resilience theory in psychology. The analysis shows that Christian spirituality—especially through a relationship with God, prayer, faith community, and the work of the Holy Spirit—has a significant contribution to fostering holistic and sustainable resilience. This article offers an integration of faith and mental health as a transformative approach to facing life's challenges.